45‐3: Four‐Plane Near‐Eye Display without Sacrificing the Frame Rate. Issue 1 (29th May 2019) - Xiong, Jianghao; Tan, Guanjun; Zhan, Tao; Lee, Yun-Han; Wu, Shin-Tson
Abstract : We build a four‐plane near‐eye display (NED) system with a passive Pancharatnam‐Berry lens and two polarization‐modulated LCDs combined by a non‐polarizing beam splitter. The system well addresses the vergence‐accommodation conflict. At the same time, it provides adequate planes to render high quality 3D scenes without sacrificing the frame rate due to passive addressing. The system can be incorporated into head mounted displays like virtual reality and augmented reality to provide vivid and comfortable 3D experience.